A Very Rare Case of Necrotizing Fasciitis Caused by Metallosis. (June 2023) - Huang, Dun-Wei; Liu, Nien-Tzu; Liu, Hung-Hui; Dai, Niann-Tzyy; Chen, Shyi-Gen; Tzeng, Yuan-Sheng
Necrotizing fasciitis is a surgically diagnosed infection of the deep soft tissues that results in high mortality. It is usually caused by aerobic and anaerobic bacteria and group A Streptococcus . Metallosis is characterized by the deposition of metal debris in the blood that causes metal poisoning and tissue damage. The abrasion of metal components that occurs after joint replacements causes metallosis, which may lead to severe complications. We report a rare case of metallosis-induced necrotizing fasciitis of the right thigh. Metallosis should be considered as a cause of necrotizing fasciitis if the patient has had a joint replacement surgery.